(untitled) (Cardiovascular Journal, 2020)
We report a 52-year-old and weight of 79.36 lbs female patient with Thrombocytopenia induced by giant atrial thrombus in rheumatic mitral stenosis. The patient underwent bioprosthetic mitral valve implantation and removal of the giant thrombus. The platelet count progressively increased achieving normal levels one week after surgery. Cardiovasc. j. 2020; 13(1): 95-96